Comparative Analysis Of Imagery and Themes In Shakespearean Tragedies and Ulugbek’s Works - M.I.Gadoeva; Z.Nurulloeva (Pubmedia Social Sciences and Humanities, 2025)
This article explores the intriguing intersection of literary expression across distinct cultural and linguistic landscapes, specifically examining shared imagery and thematic resonances between William Shakespeare’s tragedies and the works of the Timurid scholar-ruler, Ulugbek. Utilizing a comparative analysis approach, this research investigates how universal archetypal images such as darkness and light, celestial bodies, nature, and the passage of time are employed to convey profound ideas about human existence, morality, and fate within their respective literary traditions. The study reveals that despite notable cultural and linguistic disparities, certain archetypal symbols resonate across both traditions, although their interpretations and contextual significance diverge significantly. Through a close examination of key passages and literary devices, this paper highlights the profound influence of cultural perspectives and explores the nuanced tapestry of human experience mirrored in both the English and Uzbek literary contexts. The article concludes by acknowledging the challenges and rewards of comparative literature and by exploring its contribution to the broader understanding of universal human concerns